Observed and perceived benefits of providing physical activity opportunities in elementary schools: a qualitative study - Walker, Timothy J.; Craig, Derek W.; Pfledderer, Christopher D.; Robertson, Michael C.; Cuccaro, Paula; Fumero, Keisey; Bartholomew, John B. (Frontiers in Sports and Active Living, 2023)
Introduction Schools play an important role in promoting physical activity for youth. However, school-based physical activity opportunities often compete with other academic priorities, limiting their implementation. The purpose of this study was to qualitatively explore elementary school teacher and staff perspectives on providing physical activity opportunities and how they impact students and learning. Methods We partnered with a school district in Texas to conduct semi-structured individual interviews. We used a purposeful sampling approach to recruit elementary teachers and staff knowledgeable about the physical activity opportunities provided at their school. Interviews included questions about participant opinions of providing physical activity opportunities and the types of opportunities provided. We analyzed data using a directed content analysis and iterative categorization approach. Results Fifteen participants (4 teachers, 4 physical education teachers, 3 assistant principals, and 4 principals) completed interviews from 10 elementary schools. Participants discussed observed and perceived benefits when providing physical activity opportunities, which emerged into four themes and subthemes: (1) academic benefits (learning readiness, learning engagement, and academic performance); (2) social-emotional benefits (behavior, interpersonal and social skills, and classroom culture); (3) physical benefits (brain health, skill development, physical health); and (4) instructional benefits (quality teaching time, helpful teaching tools, and teacher-student relationships). Conclusions Teachers and staff observed numerous benefits when students had opportunities to be physically active, including the positive impact on academic and social-emotional outcomes. Our findings highlight the alignment of physical activity with other school priorities. Physical activity programming can be used in ways to support academics, learning, behavior, and other important outcomes.